Development of thrombocytopenia during first-line treatment and survival outcomes in newly diagnosed multiple myeloma. Issue 12 (15th October 2019) - Mellors, Patrick W.; Binder, Moritz; Buadi, Francis K.; Lacy, Martha Q.; Gertz, Morie A.; Dispenzieri, Angela; Hayman, Suzanne R.; Kapoor, Prashant; Gonsalves, Wilson I.; Hwa, Yi L.; Fonder, Amie; Hobbs, Miriam; et al.
Abstract: The prognostic significance of novel agent-induced thrombocytopenia in newly diagnosed multiple myeloma (MM) is unknown. We identified 665 newly diagnosed patients receiving proteasome inhibitors and/or immunomodulators with pretreatment platelet counts ≥100, 000/µL. Median progression-free survival (PFS) was 1.88 years (95% CI 1.48–2.38) for patients who developed treatment-related thrombocytopenia (<100, 000/µL) within sixty days of initiation of first-line therapy, compared to 2.64 years (95% CI 2.39–2.78) in patients who did not ( p  = .042), while median overall survival (OS) was 5.70 years (95% CI 3.02–9.00) and 8.43 years (95% CI 6.62–9.17), respectively ( p  = .030). Platelet count reduction >70% from pretreatment baseline was similarly predictive of inferior PFS and OS. This is the first study to demonstrate the predictive and prognostic value of treatment-related thrombocytopenia in newly diagnosed MM.